2023
DOI: 10.1002/idm2.12105
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte engineering and material modification for graphite‐based lithium‐ion batteries operated at low temperature

Abstract: Graphite offers several advantages as an anode material, including its low cost, high theoretical capacity, extended lifespan, and low Li+‐intercalation potential. However, the performance of graphite‐based lithium‐ion batteries (LIBs) is limited at low temperatures due to several critical challenges, such as the decreased ionic conductivity of liquid electrolyte, sluggish Li+ desolvation process, poor Li+ diffusivity across the interphase layer and bulk graphite materials. Various approaches have therefore be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 126 publications
0
4
0
Order By: Relevance
“…It is expected to favour a high fraction of anion‐derived inorganic components in the interphases [22] . We also observe the participation of the SN additive in Na + ‐solvation as suggested by the distinct shift to a higher wavenumber for the SN Raman band upon adding SN into the electrolyte (Supplementary Figure S1b) [12a,23] . The participation of oxidation‐stable SN molecules in Na + ‐solvation is expected to inhibit solvents’ decomposition and to increase the high‐voltage electrolyte stability, as discussed below.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…It is expected to favour a high fraction of anion‐derived inorganic components in the interphases [22] . We also observe the participation of the SN additive in Na + ‐solvation as suggested by the distinct shift to a higher wavenumber for the SN Raman band upon adding SN into the electrolyte (Supplementary Figure S1b) [12a,23] . The participation of oxidation‐stable SN molecules in Na + ‐solvation is expected to inhibit solvents’ decomposition and to increase the high‐voltage electrolyte stability, as discussed below.…”
Section: Resultsmentioning
confidence: 56%
“…We further performed nuclear magnetic resonance (NMR) and Raman spectroscopy studies for insights into the altered electrolyte solvation behaviour by the introduction of EP. First, the 23 Na NMR spectra exhibit a gradual downfield shift as the volume ratio of EP increases from 10 % to 50 %, indicating the participation of EP in solvating Na + (Figure 1d). [20] The finding is further supported by the Raman spectroscopic study.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, previous reports have demonstrated that the EC forms an organic-rich SEI, which results in an increase in interphase impedance . On the other hand, if the EC gets oxidized at a high voltage of >4.4 V (vs Li + /Li) irreversibly, lithium cobalt oxide (LCO) can only provide a specific capacity of less than 150 mAh g –1 with the cutoff voltage of 4.3 V. Furthermore, during the deep delithiation of LCO at a high voltage, with the assistance of the EC-based electrolytes, the dissolved Co 4+ further facilitates the side reaction of the electrolyte on the surface of the electrode, giving rise to the thick cathode electrolyte interphase (CEI) and high impedance as well. Therefore, it is necessary to improve the slow lithium-ion intercalation kinetics and the electrochemical window through the electrolyte design. …”
Section: Introductionmentioning
confidence: 99%
“…[14] Despite the above advantages, the large radius of K + (1.38 Å) hampers its insertion into electrode materials and induces significant volume changes during electrochemical reactions, incurring cracking or pulverization of electrode materials. [15][16][17] Various anode materials, such as carbonaceous materials, [18][19][20] metal alloys, [21][22][23] metal oxides, [24,25] and metal sulfides, [26][27][28][29] have been extensively studied. Among them, transition metal sulfides are attractive candidates due to their high theoretical specific capacity, low electronegativity, unique crystal structure, and good redox activity.…”
mentioning
confidence: 99%